IMPACT OF OFF-HOURS PRESENTATION ON DOOR-TO-BALLOON TIME AND CLINICAL OUTCOMES IN PATIENTS REFERRED FOR PRIMARY PERCUTANEOUS CORONARY INTERVENTION - SHAHZAD , MMK; JAVAID , SY; YASIN , M; JAFFRI, SKA; IQBAL, MH; SAEED , M (Biological and Clinical Sciences Research Journal, 2024)
Timely intervention is crucial in managing ST-elevation myocardial infarction (STEMI) patients undergoing primary percutaneous coronary intervention (PCI). Due to staffing and logistical constraints, off-hours presentations may impact door-to-balloon (D2B) time and clinical outcomes. Objectives: To assess the impact of off-hours presentation on door-to-balloon time and clinical outcomes in patients referred for primary percutaneous coronary intervention. Methods: After receiving approval from the Ethical Committee of the Department of Cardiology, Armed Forces Institute of Cardiology, and NIHD, 92 patients meeting inclusion criteria were enrolled, with written informed consent obtained. Participants underwent a detailed history review and physical examination. The study divided participants into off-hours and regular-hours groups based on their hospital arrival times. The main focus was on the timing of presentation, linked to outcomes like door-to-balloon (D2B) time, mortality, and complications such as cardiogenic shock and heart failure. Data on demographics, clinical characteristics, and PCI details were carefully collected using standardized forms by trained personnel. Results: The off-hours group had a mean age of 58.8 years, with 76.1% male, while the regular hour’s group had a mean age of 54.7 years and 69.6% male. Hypertension was present in 37% of the off-hours group and 41.3% of the regular-hour group. Smokers comprised 67.4% of the off-hours group and 45.7% of the regular-hours group. The off-hours group had a mean door-to-balloon time of 89.96 minutes, compared to 83.46 minutes for the regular hour group. Mortality was 4.3% in the off-hours group and 8.7% in the regular-hour group. The Cardiogenic shock occurred in 6.5% of the off-hours group versus 10.9% in the regular-hour group. Multivariable regression showed that off-hours presentation increased D2B time by 12.6 minutes. Logistic regression revealed no significant differences in mortality, shock, or heart failure between the two groups. Both groups had similar angiography findings, with most lesions in the LAD. Conclusion: Off-hours presentations result in longer D2B times for STEMI patients, mainly due to staffing and logistical challenges. However, the off-hours group had lower mortality and cardiogenic shock rates, likely influenced by disease severity and post-procedural care. Although no significant outcome differences were observed, there was a trend toward more adverse events. These findings highlight the importance of improving off-hours care, optimizing pre-hospital processes, and promoting public health initiatives.